Vaccination with staphylococcal protein A protects mice against systemic complications of skin infection recurrences - Mandelli, Andrea Paola; Magri, Greta; Tortoli, Marco; Torricelli, Stefania; Laera, Donatello; Bagnoli, Fabio; Finco, Oretta; Bensi, Giuliano; Brazzoli, Michela; Chiarot, Emiliano (Frontiers in Immunology, 2024)
Skin and soft tissue infections (SSTIs) are the most common diseases caused by Staphylococcus aureus (S. aureus), which can progress to threatening conditions due to recurrences and systemic complications. Staphylococcal protein A (SpA) is an immunomodulator antigen of S. aureus which allows bacterial evasion from the immune system by interfering with different types of immune responses to pathogen antigens. Immunization with SpA could potentially unmask the pathogen to the immune system, leading to the production of antibodies that can protect from a second encounter with S. aureus, as it occurs in skin infection recurrences. Here we describe a study in which mice are immunized with a mutated form of SpA mixed with the Adjuvant System 01 (SpAmut/AS01) before a primary S. aureus skin infection. Although under these conditions mice are not protected from the infection, they are able to mount a broader pathogen-specific functional immune response that results in protection against systemic dissemination of bacteria following a S. aureus second infection (recurrence). We show that this "hidden effect" of SpA can be partially explained by higher functionality of induced anti-SpA antibodies, which promotes better phagocytic activity. Moreover, a broader and stronger humoral response is elicited against several S. aureus antigens that during an infection are masked by SpA activity, which could prevent S. aureus spreading from the skin through the blood.